Reformasi Birokrasi Dalam Pelayanan Publik pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Padang Panjang - Falahuddin Falahuddin; Aldri Frinaldi (Jurusan Ilmu Administrasi Negara, 2020)
This study aims to determine how the implementation of bureaucratic reform at the Investment Service and One Stop Integrated Services (DPMPTSP) in Padang Panjang City and offer several solutions to improve licensing administration services related to public services. This research approach is qualitative with the type of instrumental case studies. The results showed that the implementation of bureaucratic reform in licensing administration services, from the institutional aspect, that the licensing service in Padang Panjang City was in the form of One Stop Integrated Services; Aspects of Human Resources, namely the qualifications of existing employees are not in accordance with the needs of the organization, discipline and responsibility of employees are still relatively low; Aspects of systems and procedures, where permits are generally completed beyond the specified time period, there are discrimination and inconsistencies. The quality of public services as a whole still has to be improved because the level of public satisfaction is still categorized as sufficient. Where we can see the influential relationship between the quality of services performed by officers and community satisfaction as service recipients. In the future, it is hoped that it will be important that DPMPTSP Kota Padang Panjang improve the quality of its services to achieve public satisfaction.